2015
DOI: 10.1002/eqe.2570
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐element analysis of laminated rubber bearing of building frame under seismic excitation

Abstract: SUMMARYFinite element analysis is carried out for a building frame supported by laminated rubber bearings to simultaneously investigate global displacement and local stress responses under seismic excitation. The frame members and the rubber bearings are discretized into hexahedral solid elements with more than 3 million degrees of freedom. The material property of rubber is represented by the Ogden model, and the frame is assumed to remain in elastic range. It is shown that the time histories of non-uniform s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The calibration of the models of steel-laminated elastomeric bearings analysed in this paper was based on the study of Ohsakiet al [36]. The latter numerical models were developed in ABAQUS and compared against results available in the literature [36] [47]. This calibrated numerical model was considered to be the reference of this study.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration of the models of steel-laminated elastomeric bearings analysed in this paper was based on the study of Ohsakiet al [36]. The latter numerical models were developed in ABAQUS and compared against results available in the literature [36] [47]. This calibrated numerical model was considered to be the reference of this study.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…global tension as described by Mitoulis [7], Tubaldi et al [25] and Mitoulis et al [26] for bridge bearings, or local tensile effects. With regard to international literature, emphasis was placed on the shear and compressive response of the isolators under design basis earthquakes by performing numerical tests and experiments [7] [26][27][28][29][30][31][32][33][34], whilst less emphasis was placed on the tensile response of the isolators [4] [6] [31][32][33][34][35][36][37][38]. Additionally, Cardone & Perone [39] based their research on the assumption that there is no development of tensile stresses in the bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Warn et al performed parametric finite element analyses, and suggested that the critical load capacity is influenced by not only the overlapping area, but also the shape factor of the bearing and Weisman et al conducted experimental tests and finite element analyses, and showed that the overlapping area method is a conservative estimation . In addition, Ohsaki et al performed finite element analyses for a building frame supported by rubber bearings which showed that the vertical pressure concentrates at the overlapping area .…”
Section: Introductionmentioning
confidence: 99%
“…The theories and steps of baseisolated structure with rubber-bearing design were introduced by Tian et al, [4] the hysteretic curve show that structures with high damping rubber bearing and base isolation system can absorb the earthquake energy most effectively. Finiteelement analysis of laminated rubber bearing of building frame under seismic excitation was done by Ohsaki et al, [5] It was found that FE-analysis is indispensable tool for analysis and design of laminated rubber bearings. Incorporation of damping, softening property, and effect of temperature change for lead and high-damping rubber bearings remains to be investigated in future research.…”
Section: Literature Reviewmentioning
confidence: 99%